SAT0217 Axon Reflex Vasodilatation of Digital Arteries in Systemic Sclerosis Patients, Evaluated by Laser-Doppler Fluxmetry. (15th July 2016) - Rotondo, C.; Nivuori, M.; Chialà, A.; Praino, E.; Coladonato, L.; Anelli, M.G.; Giannini, M.; Lascaro, N.; Fanizzi, R.; Laselva, G.; Cacciapaglia, F.; Lapadula, G.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a connective disease characterized by severe microvessels vasculopathy. The important role of endothelial dysfunction in SSc pathogenesis is widely demonstrated, but the SSc related autonomic nervous system impairment is controversial and rarely described. The dysregulation of axon reflex vasodilatation of fingertip microvessels in SSc has been reported in some studies, but the functional involvement of digital arteries in SSc patients had never been investigated. Objectives: We aimed at evaluating the blood flux changes mediated by axon reflex response upon heating stimulus in SSc patients. Methods: 87 SSc patients (SSc pt) and 22 healthy controls (HC) were recruited in this study. The SSc patients were aged 52, 7±16, 2 yrs, with disease duration of 8, 23±7, 8 yrs. The LD Flowmetry (Periflux System 5000, Perimed) with 4 LD heating probes was used to measure the skin blood flux of the middle phalanx of the 2nd, 3rd, 4th and 5th fingers of the left hand. The skin fingers flux was recorded at pre-heating period with probes temperature fixed at 34 °C (PHF) and after 5 min heating at 44 °C (IHF). Therefore, the heating test assesses the variation of digital artery flux in response to local heating stress at 44 °C. The ratio IHF/PHF evaluates the axon reflex mediated vasodilatation (ARMV). The results are expressed as average across 4 fingers at each time. The flux was expressed in perfusion unit (PU) and HC and SSc patients responses were compared by the t-student test. Statistic significance was set at p≤0, 05. The data analysis was performed using IBM SPSS statistic 20. Results: The ARMV was significantly reduced in SSc patients (2, 2±1, 4) in comparison with HC (4, 8±2, 7, p=0, 0001). IHF was lower in SSc patients (118, 6±54, 3) than HC (168±78, p=0, 001). Dividing the SSc pts group by the presence of pitting scars (PS), digital ulcers (DU) and digital necrosis (DN), we observed a lower IHF in SSc pts with PS (103, 2±48, 6) than in SSc pts without (138, 1±56, p=0, 003), and in SSc pts with DU (97, 8±47, 6) than in SSc pts without (160, 27±120, 1, p=0, 002). Moreover, SSc pts with ND showed a lower ARMV (1, 8±1) than SSc pts without (2, 6±1, 5, p=0, 006), and a lower IHF (98, 3±49, 1 vs 133, 2±54, 5, p=0, 004). The age, sex, concomitant therapy with Ca-antagonist or Bosentan or cardioaspirin did not influence the digital artery flux. Conclusions: This study provided evidence that a functional impairment of DA occurs in SSc, and it worsens with increasing severity of vascular clinical manifestations. Disclosure of Interest: None declared